Application of lymphoplasmapheresis in the treatment of severe myasthenia gravis - Duan, Weiwei; Zhou, Hao; Dong, Xiaohua; Li, Bijuan; Li, Yi; Cai, Haobing; Zhou, Qian; Ouyang, Song; Yin, Weifan; Yang, Huan (Frontiers in Neurology, 2022)
Background: Lymphoplasmapheresis (LPE) is a treatment that combines traditional plasma exchange and lymphocyte removal technique. It has been applied to treat a variety of autoimmune diseases, but its application value in the treatment of severe myasthenia gravis (MG) is not yet clear. Therefore, the aim of this study was to investigate the efficacy and safety of LPE in severe MG. Methods: Clinical data of 123 severe MG patients (Myasthenia Gravis Foundation of America Clinical Classification, Class IV) who received LPE treatment were included in a retrospective analysis. Efficacy was evaluated by the change of Quantitative Myasthenia Gravis score (QMGS) before and after treatment. Univariate and multivariate logistic regression analysis was used to explore clinical factors affecting efficacy. Results: A total of 220 replacements were performed in 123 patients. The overall safety of LPE was good, and no serious adverse reactions occurred. After treatment, the mean QMGS of patients decreased significantly, from 23.40 ± 4.25 points before treatment to 17.93 ± 5.61 points after treatment, a decrease of 5.47 ± 4.16 points. 75.6% of patients experienced remission of clinical symptoms. Each muscle group involved in MG responded well to LPE treatment. Age ≥50 years and co-infection were unfavorable factors affecting the efficacy. Conclusions: LPE is safe for the treatment of severe MG and achieves good treatment outcome with fewer replacements. In MG patients, the avoidance and timely control of infection are necessary. Our study provides a new treatment option for severe MG.